Evaluating Risk of Recurrent Venous Thromboembolism During the Anticoagulation Period in Patients with Malignancy - Louzada, Martha (Université d'Ottawa / University of Ottawa, 2011)
Background - Current guidelines suggest that all cancer patients with venous thrombosis be treated with long-term low molecular weight heparin. Whether treatment strategies should vary according to clinical characteristics remains unknown. // Systematic review - A systematic review was performed to determine current understanding of the association between malignancy characteristics in patients with cancer-associated VTE and the risk of VTE recurrence. Four retrospective and 6 prospective studies were included. They suggest that lung cancer, metastases, and adenocarcinomas confer an increased the risk of recurrence and breast cancer a low risk. // Survey - I performed survey to evaluate thrombosis experts’ opinion about the low risk of VTE recurrence they would consider acceptable for patients with cancer- associated thrombosis 103 specialists participated. 80% of respondents agreed that a risk of recurrent VTE during anticoagulation below 7% is low enough. 92% agreed that a CPR that categorizes risk of recurrence is relevant. // Retrospective Study - I performed a single retrospective cohort study to assess the feasibility of derivation of a CPR that stratifies VTE recurrence risk in patients with cancer–associated thrombosis. The study included 543 patients. A multivariate analysis selected female, lung cancer and prior history of VTE as high risk predictors and breast cancer and stage I disease as low risk. // Conclusion - Patients with cancer-associated thrombosis do have varying risks of recurrent VTE depending on clinical characteristics.
Keywords: venous thromboembolism recurrence; cancer; malignancy; risk factors; clinical prediction rule